Transmission Error and strain analysis of lightweight gears by using a hybrid FE-analytical gear contact model. (15th May 2019) - Shweiki, Shadi; Rezayat, Ali; Tamarozzi, Tommaso; Mundo, Domenico
Highlights: An efficient multibody formulation of the gear mesh stiffness is developed. An FE description of the gear deformation field allows to recover the strain field. The effects of a lightweight body geometry on the meshing behaviour are analysed. A good correlation is achieved between numerical predictions and experiments. Abstract: In this paper the transmission error and the strain field are analysed for two gear pairs, with different lightweight designs, reflecting the common industrial practice. The methodology used for the analysis is based on a hybrid FE-Analytical approach implemented in a multibody solver which allows to achieve a good accuracy with a low computational effort. The specific formulation allows to well describe the deformation field of the gear body from which the strain values can be computed at specific locations in the FE model. The numerical method used in this work is validated both in terms of transmission error and strain field, using the results obtained from an experimental campaign performed on a high-precision gear test rig.